Organic carbonate production utilizing crude glycerol derived as by-product of biodiesel production: A review - Nomanbhay S.; Ong M.Y.; Chew K.W.; Show P.-L.; Lam M.K.; Chen W.-H. (MDPI AG, 2023)
Biodiesel; Carbonation; Irradiation; Microwave irradiation; Reaction kinetics; Alternative materials; Biodiesel production; Biomass resources; Crude glycerol; Dimethyl carbonate; Glycerol carbonate; Organic carbonates; Production methods; Glycerol